Siyasah Maliyah Review of Baznas Position in Zakat Management After the Constitutional Court Decision Number 54/PUU-XXIII/2025 - Muhammad Azwar Fajrurrahman; Lutfi Fahrul Rizal; Budi Tresnayadi (al-Afkar, Journal For Islamic Studies, 2026)
Zakat governance in Indonesia has been institutionally strengthened through Law Number 23 of 2011, which designates the National Zakat Agency (BAZNAS) as the primary authority in national zakat management. This arrangement raises institutional concerns because BAZNAS performs dual roles as both regulator and operator. The debate intensified following Constitutional Court Decision Number 54/PUU-XXIII/2025, which rejected a judicial review petition against BAZNAS’s authority. This study aims to analyze the legal position of BAZNAS in Indonesia’s zakat management system, examine the implications of Constitutional Court Decision Number 54/PUU-XXIII/2025, and assess BAZNAS’s dual functions from the perspective of siyasah maliyah. This research employs a normative legal method using statutory, conceptual, and Islamic legal approaches. Data sources include legislation, Constitutional Court decisions, classical Islamic legal literature, and relevant academic journals. The findings reveal that BAZNAS’s dual function is constitutionally valid; however, from the perspective of siyasah maliyah, it requires stronger accountability, transparency, and distributive justice to ensure that zakat governance remains aligned with public welfare principles.